Pengaruh Promotion Mix terhadap Keputusan Mahasiswa Baru dalam Memilih Kuliah di STP Bogor - Dinitri, Seruni; Adillah, Brian; Irfan, Muhammad (Prasetiya Mulya Publishing, 2024)
The world of higher education is an institution that is increasingly competing with each other, both in terms of quantity and quality. Nowadays, many private educational institutions are experiencing difficulties in finding student’s intake. This condition aggravated by Covid-19 pandemic situation where many prospective students and even active students find it difficult to continue their education further. The impact of the Covid-19 pandemic is still being felt today because the number of students is decreasing. Sekolah Tinggi Pariwisata Bogor, a private educational institution, has been carried out various promotions to aggravate new student’s intake, but it is necessary to analyze the effectiveness of the promotions that have been carried out. This research was conducted to find out how promotion mix and which elements from promotion mix that influence the most for new students' decisions in choosing to study at Sekolah Tinggi Pariwisata Bogor. This research uses a quantitative approach by giving questionnaires to new students (2023/2024) with a total of 196 students. The number of samples tested was 100 respondents who were analyzed using multiple linear regression analysis tests. From the analysis, it was found that all promotion mixes factors simultaneously influenced new students' decisions in choosing to study at Sekolah Tinggi Pariwisata Bogor. This shows how important the promotion mix is ​​in the decision of new students to choose to study at Sekolah Tinggi Pariwisata Bogor. However, in carrying out a partial analysis, it was found that sales promotion and public relations had a partial influence on new students' decisions. Meanwhile, Advertising, Direct Marketing, and Personal Selling were found to have no partial influence on new students' decisions. These results could give special benefit for marketing to continue improving and carrying out promotional variations, especially for sales promotion and public relations elements.